Evidence of a two-state picture for supercooled water and its connections with glassy dynamics - Appignanesi, Gustavo Adrian (2009)
The picture of liquid water as consisting of a mixture of molecules of two different structural states (structured, low-density molecules and unstructured, high-density ones) represents a belief that has been around for long time awaiting for a conclusive validation. While in the last years some indicators have indeed provided certain evidence for the existence of structurally different ``species´´, a more definite bimodality in the distribution function of a sound structural quantity would be desired. In this context, our present work combines the use of a structural parameter with a minimization technique to yield neat bimodal distributions in a temperature range within the supercooled liquid regime, thus clearly revealing the presence of two populations of differently structured water molecules. Furthermore, we elucidate the role of the inter-conversion between the identified two kinds of states for the dynamics of structural relaxation, thus linking structural information to dynamics, a longstanding issue in glass physics.